The Communication Patterns Between Parents and Migrant Children in the Digital Era: Strengthening Emotional Connections Through Technology - Sinaga, Celvin Yhosep; Watloly, Aholiab; Litaay, Simona Christina Henderika (Universitas Pattimura, 2024)
This study aims to analyze the communication patterns between parents and migrant children in the digital era and their impact on emotional connection between both parties. Digital technology provides an opportunity for parents and children to stay connected despite being separated by distance; however, the intensity of communication plays a crucial role in shaping the quality of this relationship. This research was conducted on migrant students living in dormitories at Pattimura University using a qualitative approach. Data collection techniques included observation, in-depth interviews, and documentation. The findings indicate that migrant children who frequently communicate with their parents feel more emotionally connected, experience less loneliness, and are able to develop independence and new experiences. Conversely, students with lower communication intensity tend to feel lonelier but view this as a coping strategy to stay focused on their lives away from home. Some students reported that excessive communication with parents could trigger excessive longing and a strong desire to return home. The novelty of this study lies in understanding how digital technology serves not only as a communication tool but also as an emotional bridge for families separated by distance. This study recommends that further research explore the psychological and social aspects of communication intensity and its impact on the emotional well-being of migrant children. The findings contribute to the development of social sciences and humanities, particularly in understanding the dynamics of family communication in the digital era.